Conservation Practices of Maguindanaons in Lake Buluan, Maguindanao, BARMM - Angel Dela Cruz; Amera Malaco; Cherie Mangaoang (East Asian Journal of Multidisciplinary Research, 2023)
This study was conducted to determine the conservation practices of the Maguindanaoan community in Lake Buluan, Maguindanao, BARMM.  A descriptive qualitative method was employed and a total of 50 respondents were randomly selected and interviewed using a structured questionnaire. Pearson correlation was used to assess the strength of the relationship of the variable considered. Data showed that most of the respondents are male (64%) and all are Maguindanaoan. The overall mean knowledge of biodiversity and conservation among respondents was very high, ranging from 4.21-5.00. However, the perceived attitude of the respondents towards biodiversity and conservation was medium, indicating that the majority of the respondents are aware of the loss, exploitation, and reasons of the loss of habitat of native species in the area. The overall mean of 4.16 indicates a high sense of dependent on biodiversity at Lake Buluan. It further showed a high sense of responsibility in preserving the environment, cultural homogeneity, and a high level of community belongingness in Lake Buluan. There is a significant correlation between community awareness and age, knowledge, practices, and well-being. Furthermore, the results of this study can be used as the basis for the government and policymakers in developing a more effective strategy for promoting biodiversity conservation.